Looking backward to find a path forward for the sustainable flow of suitable potato varieties to Eritrean potato farmers - Fitsumberhan Ghebremeskel Ghebreagziabiher; Monica Gorman; John Burke; Paul C. Struik; Denis Griffin (International Journal of Agricultural Sustainability, 2022)
The lack of a sustainable flow of suitable potato varieties is a major contributing factor to low productivity and production of potato in Eritrea. This study examined the history of potato variety introductions to identify weaknesses, a path forward and enable the sustainable flow of suitable potato varieties to potato farmers. The research approaches included: reviewing the history of potato variety introductions to Eritrea, consultation with local and international stakeholders and a survey assessing potato variety preference. Over 70 varieties of potato have been introduced and 14 varieties approved through the official system but with only three currently available. Many farmers rely on poor-quality seed from unofficial sources. The analysis led to the identification of priorities for improvement: strengthening research institutions to create networks for potato variety sourcing; strengthening local regulatory institutions to implement registration and release standards; engaging potato farmers in the variety evaluation process; considering Plant Variety Protection and Plant Breeders Rights when establishing potato variety conservation; designing maintenance and multiplication strategies and also allowing the private sector to participate in potato variety seed sourcing and distribution. These options could be the basis of a roadmap making improved potato varieties and seeds available to potato farmers in Eritrea.